Optimal Redistributive Wealth Taxation When Wealth Is More Than Just Capital - Max Franks; Ottmar Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2020)
We show how normative standpoints determine optimal taxation of wealth. Since wealth is not equal to capital, we find very different welfare implications of land rent-, bequest- and capital taxation. It is mainly land rents that should be taxed. We develop an overlapping generations model with heterogeneous agents and calibrate it to OECD data. We compare three normative views. First, the Kaldor-Hicks criterion favors the laissez-faire equilibrium. Second, with prioritarian welfare functions based on money-metric utility, high land rent taxes are optimal due to a portfolio effect. Third, if society disapproves of bequeathing, bequest taxation becomes slightly more desirable.
Keywords: D31; D63; E62; H21; H23; Q24; 330; optimal taxation; social welfare; wealth inequality; land rent tax; Georgism